Assessment of Academic Staff Performance in English Medium Instruction - Vita Kalnbērziņa; Indra Karapetjana (Baltic Journal of English Language, Literature and Culture, 2021)
One of the internationalisation strategies for higher education institutions is internationalisation of their curricula by delivering English-medium instruction programs. These internationalization efforts can be successful if support for the language needs of all stakeholders involved is provided. English language proficiency assessment of academic staff is an essential prerequisite to the implementation of a high-quality study process in the English language. Therefore, the aim of this paper is to validate the assessment system of academic staff performance in English medium instruction at a university in Latvia and the use of mediation strategies as a basis for the assessment system development. The qualitative and quantitative analysis of the test results suggests that the integrated assessment tasks demonstrate higher internal consistency and higher correlation with the test results and the performance of the academic staff in the international setting.